Interplay of transitions between oscillations with emergence of fireballs and quantification of phase coherence, scaling index in a magnetized glow discharge plasma in a toroidal assembly. (January 2018) - Saha, Debajyoti; Ghosh, Sabuj; Shaw, Pankaj Kumar; Janaki, M.S.; Iyengar, A.N.S.
Highlights: Interplay of transition of floating potential fluctuations in a glow discharge plasma in the toroidal vacuum vessel of SINP tokamak has been observed. Display of dominant frequencies with the variation in discharge voltage, vertical, toroidal, mixed magnetic field (vertical+toroidal) has been carried out to understand about the frequency information. Evolution of associated anode fireball dynamics under the action of increasing vertical, toroidal as well as increasing vertical magnetic field at a fixed toroidal magnetic field (mixed field) of different strength has been studied. Estimation of phase coherence index for each case has been carried out to examine the evidence of finite nonlinear interaction. A comprehensive study of the dynamics of the fireball is found to be associated with the values of phase coherence index. The index is found to take maximum values for the case of toroidal, mixed magnetic field when there is an existence of power/energy concentration in a large region of frequency band. The scaling exponent associated with this floating potential fluctuations has been illustrated using the detrended fluctuation analysis (DFA) algorithm. Interplay of transitions between oscillations lead to the toggling from correlated dynamics to long range persistence as ensured from the results of DFA. The persistence long range behaviour in presence of higher toroidal magnetic field corresponds to the pear shaped glow. Abstract: Interplay of transition of floating potential fluctuations in a glow discharge plasma in the toroidal vacuum vessel of SINP tokamak has been observed. With variation in the strength of the vertical and toroidal magnetic fields, regular and inverted relaxation oscillations as well as sinusoidal oscillations are observed with the slow and fast time scale of the relaxation oscillations reversing their nature at a high value of vertical magnetic field strength. However for small value of toroidal magnetic field the transitions follow relaxation  →  chaotic oscillations with the chaotic nature prevailing at higher values of toroidal magnetic field. Evolution of associated anode fireball dynamics under the action of increasing vertical, toroidal as well as increasing vertical field at a fixed toroidal field (mixed field) of different strength has been studied. Estimation of phase coherence index for each case has been carried out to examine the evidence of finite nonlinear interaction. A comprehensive study of the dynamics of the fireball is found to be associated with the values of phase coherence index. The index is found to take maximum values for the case of toroidal, mixed field when there is an existence of power/energy concentration in a large region of frequency band. A detailed study of the scaling region using detrended fluctuation analysis (DFA) by estimating the scaling exponent has been carried out for increasing values of discharge voltage (DV), vertical, toroidal as well as the mixed field (toroidal plus vertical). A persistence long range behaviour associated with the nature of the anode glow has been investigated in case of higher values of toroidal, mixed field whereas increasing DV, vertical magnetic field lead to a perfectly correlated dynamics with values of scaling exponent greater than unity.